The Relationship Between Dysmenorrhoea and Student Learning Activities at SMA Negeri 3 Palembang - Ali Ar Ridha Molahella; Hartati (Community Medicine and Education Journal, 2020)
Dysmenorrhea is a menstrual disorder often faced by adolescent girls. In some people with dysmenorrhoea, perceived pain can interfere with daily physical activity giving the impact on quality of life and productivity of students in the school. This study aims to determine the relationship between dysmenorrhea and learning activities at SMA Negeri 3 Palembang. This study was an analytic observational study with cross sectional design conducted in November-Desember 2015. The population in this study were all students of SMA Negeri 3 Palembang. The samples were obtained by total sampling with total sample of 631 female student. Data were obtained through a questionnaire given to respondents. The results were analyzed by using Fisher's Exact Test. From this study, the prevalence of students who suffer from dysmenorrhea was 91.3%. Number of respondent with dysmenorrhea and disturbed study activity was 56.4%. Results of bivariat analysis showed a highly significant relationship between dysmenorrhea and study activity (p=0.000).